Opportunities to Implement Traditional Games as Contextualized Physics Learning Innovations - Luthfiyaul Laila; Ladika Zuhrotul Wardi; Utama Alan Deta (Reog: Journal of Ecoethnoscience Education, 2025)
One of the main challenges in developing traditional game-based physics learning is that it is not yet known how students perceive the approach. Students' perceptions, interests, and readiness are crucial aspects that need to be mapped before developing a targeted learning strategy. Therefore, this study aims to identify and analyze how students respond to traditional game-based physics learning through science literacy, the level of interest generated, and their readiness to be actively involved in the learning process with this approach. This study uses a descriptive qualitative approach, the study was conducted in one of the high schools in Sidoarjo City, with 100 students in grade XI purposively selected to represent a diversity of academic and social characteristics. Data were collected through observation, questionnaires, and interviews. Most students indicated that they still have difficulties in understanding and linking physics concepts with daily life and technology. The majority of students are interested and motivated to learn physics when learning is packaged in an engaging, creative, and fun way. However, they also expressed higher interest when learning is done through experiments and games, although most students had never experienced physics learning using traditional games, they showed an open and positive attitude towards the approach. The conclusion is idea of physics learning based on traditional games received a positive response from students. This approach can increase interest and motivation to learn and also opens up great opportunities to improve science literacy and active participation of students in a meaningful and contextualized learning process. Although there are some challenges in linking concepts with local cultural contexts, these obstacles can be overcome by designing appropriate learning oriented to students' experiences.